2020
DOI: 10.1101/2020.09.12.294348
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RANKL from Bone Marrow Adipose Lineage Cells Promotes Osteoclast Formation and Bone Loss

Abstract: Receptor activator of NF-κB ligand (RANKL) is essential for osteoclast formation. The cellular source of RANKL for osteoclastogenesis has not been fully uncovered. Bone marrow (BM) adipocytes derived from bone marrow mesenchymal stromal cells (BMSCs) express RANKL. Here we demonstrated that the AdipoqCre could target bone marrow adipocytes. We crossed the AdipoqCre mice with ranklfl/fl mice to conditionally delete RANKL from BM adipocytes. Conditional deletion of RANKL increased cancellous bone mass in the lon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 48 publications
(86 reference statements)
1
13
0
Order By: Relevance
“…Additionally, unlike bone marrow AdipoQ+ progenitors, these peripheral AdipoQ+ cells nearly do not produce M-CSF. The cells producing RANKL usually appear to simultaneously express M-CSF, such as osteocytes and bone marrow AdipoQ-lineage progenitors (our findings and (21,(27)(28)(29)). This is not the case for peripheral AdipoQ+ adipocytes, which express neither RANKL nor M-CSF (our findings and ( 29)).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Additionally, unlike bone marrow AdipoQ+ progenitors, these peripheral AdipoQ+ cells nearly do not produce M-CSF. The cells producing RANKL usually appear to simultaneously express M-CSF, such as osteocytes and bone marrow AdipoQ-lineage progenitors (our findings and (21,(27)(28)(29)). This is not the case for peripheral AdipoQ+ adipocytes, which express neither RANKL nor M-CSF (our findings and ( 29)).…”
Section: Discussionsupporting
confidence: 64%
“…In this study, we identified bone marrow AdipoQ-lineage progenitors as a new cellular source of M-CSF expression, which contributes substantially to the bone marrow macrophage development, physiological bone mass maintenance and pathological bone destruction via controlling osteoclast formation. Bone marrow AdipoQ-lineage progenitors also produce RANKL (27)(28)(29), an essential cytokine to induce osteoclast differentiation. These findings collectively highlight the significance of bone marrow AdipoQ-lineage progenitors in the regulation of osteoclastogenesis and bone metabolism, as well as the potential translational implications of appropriately targeting this cell population in treating pathologic bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…In our mouse model, we also highlighted an unexpected increase in BMAT in both heterozygous and homozygous knock-in mice. Two different studies reported independently that BMAT-derived RANKL induces osteoclastogenesis and bone remodelling, indicating that excessive RANKL generated by bone marrow adipocytes is an underlying cause of skeletal disorders 37,38 . Therefore, we cannot exclude a positive effect of the mutation on BMAT that further boosts osteoclast differentiation and therefore results in a more aggressive phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, computational analysis revealed MALPs to be the most interactive mesenchymal cells with monocyte-macrophage lineage cells due to their high and specific expression of several osteoclast regulatory factors, including RANKL and Csf1 (25). Studies from our group and others have demonstrated that MALP-derived RANKL is critical for promoting bone resorption during physiological and pathological conditions (25,26). Since Csf1 is also important for osteoclastogenesis, here we generated Csf1 conditional knockout mice using Adipoq-Cre driver and examine the role of MALP-derived Csf1 in bone homeostasis and diseases.…”
Section: Introductionmentioning
confidence: 99%